Institutionalizing the evaluation of health programs and policies in France: cuisine internationale over fast food and sur mesure over ready-made Institucionalizando a avaliação de programas e políticas de saúde: culinária e corte-costura nas lições francesas - Zulmira M. A. Hartz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
The purpose of this article is to describe several chronological milestones in institutionalizing the evaluation of public programs and policies in France from a governmental perspective and in the health sector, situating such references in the international context. The institutional nature of evaluation implies integrating it into an action-oriented model, linking analytical activities to management, thus constituting the formulation of an evaluation policy for policy evaluation. The study focuses on issues related to the structure, practice, and utilization of evaluation results as well as other characteristics providing the French model with a certain resistance to traditional "fast-food" or "ready-made" methodological approaches. The institutionalization of sectorial evaluation appears more promising than that of the government's centralized channel, despite the work developed by a Scientific Evaluation Council, and suggests avenues for reflection and debate pertaining to the Brazilian Unified Health System. Este texto tem o propósito de descrever alguns marcos cronológicos de institucionalização da avaliação de programas/políticas públicas da França, na perspectiva governamental e no setor saúde, contextualizando-os no âmbito internacional. O caráter institucional da avaliação supõe integrá-la em um modelo orientado para ação, ligando atividades analíticas às de gestão, constituindo assim uma formulação da política de avaliação para avaliação de políticas. São focalizadas questões relacionadas à estrutura, à prática e à utilização dos resultados da avaliação, bem como outras características que conferem ao modelo francês uma certa resistência ao "fast food" ou "prêt-à-porter" das abordagens metodológicas tradicionais. A avaliação setorial se revela mais promissora em sua instucionalização do que o dispositivo centralizado do governo, apesar do trabalho desenvolvido por um Conselho Científico de Avaliação, sugerindo pistas de reflexão e debate na perspectiva do SUS.